The Enforcement of the Illinois Felony Marijuana Law in Chicago - Richard P. Fahey (Washington University Law Quarterly, 1971)
This study looks at the enforcement of the Illinois marijuana law by the police and court having jurisdiction over the City of Chicago. Data was collected in two separate surveys during the summer of 1969, one of the Chicago Police and the other of the Circuit Court of Cook County Criminal Division's Narcotics Court. It should be noted that the purpose of this study was not to follow the same individuals as they move through the Chicago enforcement system. Rather, the purpose here was to see how the system charged with the enforcement of the marijuana law deals with the violator, and what effect the conflict between law and order has on the enforcers.
Keywords: Narcotics